The Use of Electrical Resistivity Tomography to Investigate Basaltic Lava Tunnel Based on the Case Study of Al-Badia Cave in Jordan - Al-Amoush, Hani; Abu Rajab, Jafar (Indonesian Journal on Geoscience, 2018)
DOI: 10.17014/ijog.5.2.161-177Electrical Resistivity Tomography (ERT) was employed to conduct a geoelectrical survey near the Al-Badia lava tunnel located close to the Al-Bishyrria Village in Jordan. The technique enabled the mapping of the subsurface tunnel extension and description of its inner structure. To assess the quality of data and resistivity models, Schlumberger and Reciprocal Schlumberger electrode configurations were used to produce eight ERT profiles. As revealed by the examination of received potential, the implemented configurations exhibited a strong signal, producing an approximated reciprocal error of up to 6%. The findings of ERT models showed that the lava tunnel had a clearly outlined structure with an elliptical to rectangular shape. The modelled resistivity of the lava tunnel was obtained in proximity to 1000 Î©-m, with a better characterization being possible at resistivity exceeding 8000 Î©-m in 200 Î©-m of Fahda Vesicular Basalt medium. An exploration depth of 50 m revealed that the lava tunnel was 10 m deep and 5 m in diameter on the average. Furthermore, potential means of groundwater recharging were reported by the simultaneous detection of a number of resistivity anomalies of less than 50 Î©-m and lava tunnel. In addition, the lava tunnel was observed to extend and ramify beyond the area under investigation, indicating at the potential existence of multiple lava tunnel extensions in both the investigation area and in the basaltic flows, which could have adverse implications for future urban projects.